2009
DOI: 10.1128/iai.01425-08
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni Glycosylation Island Important in Cell Charge, Legionaminic Acid Biosynthesis, and Colonization of Chickens

Abstract: Previously, we identified five genes (Cj1321 to Cj1326, of which Cj1325 and Cj1326 are a single gene) in the O-linked flagellin glycosylation island that are highly prevalent in Campylobacter jejuni isolates from chickens. We report mutagenesis, functional, and structural data to confirm that this locus, and Cj1324 in particular, has a significant contributory role in the colonization of chickens by C. jejuni. A motile ⌬Cj1324 mutant with intact flagella was considerably less hydrophobic and less able to autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
122
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 65 publications
4
122
0
1
Order By: Relevance
“…Published work relates to the formation of biofilms in the environment as a mechanism of persistence and possible transmission and survival within the poultry house (Howard et al, 2009;Svensson et al, 2009). Water in poultry houses has been shown to be a possible source of infection for birds and it has also been shown that C. jejuni is present in biofilms in drinking apparatus (Hanning et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Published work relates to the formation of biofilms in the environment as a mechanism of persistence and possible transmission and survival within the poultry house (Howard et al, 2009;Svensson et al, 2009). Water in poultry houses has been shown to be a possible source of infection for birds and it has also been shown that C. jejuni is present in biofilms in drinking apparatus (Hanning et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These so-called post-translational modification (ptm) genes are cj1324 (ptmG), cj1325/6 (ptmH), cj1327-cj1330 (ptmC, ptmD, ptmE, ptmF), cj1331 (ptmB) and cj1332 (ptmA) (McNally et al, 2007). Although knowledge of the importance of Oglycosylation by LegAm is limited, recent investigations by Howard et al (2009) gave a first insight into its biological relevance. A C. jejuni cj1324 mutant showed full motility, but less hydrophobicity and impaired autoagglutination and biofilm formation due to the absence of two LegAm glycan modifications.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also could clearly show reduced autoagglutination but no alterations in biofilm formation (data not shown). In contrast to Howard et al (2009), we did not investigate the genes cj1321-cj1323, but we examined all genes required for LegAm synthesis with regard to altered transcription. This revealed transcription of ptmB (cj1331), ptmC (cj1327) and ptmE (cj1329) to be strongly downregulated in the cj0005c mutant, whereas the transcription of genes ptmA (cj1332), ptmF (cj1330) and ptmG (cj1324) was significantly downregulated but to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial pathogens associated with enteric fever use such strategies (124), and it is noteworthy that C. jejuni can sometimes be found in deep muscle and visceral organs. C. jejuni may evade detection by avian TLR5, because mutant strains lacking genes responsible for glycosylation of the flagella elicit stronger proinflammatory cytokine responses in chick ceca and exhibit defects in intestinal persistence relative to the parent strain (125). Salmonella Typhimurium strains expressing the C. jejuni proteins CjaA or Peb1A elicit protection against intestinal colonization of chickens by C. jejuni (126), which suggests that immune control of C. jejuni in the avian intestines may be feasible.…”
Section: Campylobactermentioning
confidence: 99%